European high-speed bogie technology review. (7th August 2019) - Deng, Xiaojun; Shi, Huailong; Guo, Jinying; Zhu, Haiyan
This review presents the current technical statuses of European high-speed bogie technology and related infrastructure, in which the concepts and design solutions associated with the high-speed rolling stocks and railway are summarised. Regarding the high-speed railway infrastructure conditions, the vehicle gauges, track gauge, rail profiles, and associated inclinations for various countries and rail networks are discussed briefly, as well as the curve arrangements and track irregularities. Then four typical and widely used high-speed bogies are introduced with their design principles and solutions are discussed, in which the advantages and disadvantages of various bogie frame types, bearings, wheelset steering arrangements, and primary/secondary suspensions are thoroughly analysed. Furthermore, the brake system commonly used in European railway networks and the on-board diagnostic systems used to ensure safe operation are also discussed concerning their applicability, versatility and reliability. A general understanding of the technical specification for interoperability (TSI) is also included in this investigation.